Вместо предисловия - Fast, Piotr (Przegląd Rusycystyczny, 2020)
<span style="display: inline !important; float: none; background-color: rgba(0, 0, 0, 0.03); color: #212529; font-family: 'Segoe UI','Roboto','Oxygen-Sans','Ubuntu','Cantarell','Helvetica Neue',sans-serif; font-size: 14.4px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">Вместо предисловия